The Natural Problem of Consciousness. - Snider, Pietro (De Gruyter, 2017)
The "Natural Problem of Consciousness" is the problem of understanding why there are presently conscious beings at all. Given a non-reductive naturalist framework taking consciousness as an ontologically subjective biological phenomenon, how can we rationally explain the fact that the actual world has turned out to be one where there are presently living beings that can feel, rather than having developed as a zombie-world in which there would be no conscious experiences of any kind? This book introduces the Natural Problem by relating it to central problems in the philosophy of mind (metaphysical mind-body problem, Hard Problem of consciousness) and emphasizing the distinctive interest of its diachronic dimension. Ranging from philosophy to biology and neuroscience, it offers a thorough analysis aimed at better understanding what could explain why phenomenal consciousness has been preserved throughout evolution by natural selection. This is an original, engaging, and thought provoking philosophical study of a neglected but fundamental question regarding the nature and origin of consciousness.
Keywords: Consciousness.; Conscience.; PHILOSOPHY -- Movements -- Humanism.; Consciousness; Evolution.; mental causation.; mind-body problem.; natural selection.; phenomenal consciousness.